A highly sensitive colorimetric metalloimmunoassay based on copper-mediated etching of gold nanorods. Issue 6 (25th February 2016) - Cheng, Fangbin; Chen, Zhaopeng; Zhang, Zhiyang; Chen, Lingxin
Abstract : A highly sensitive colorimetric metalloimmunoassay based on copper-mediated etching of gold nanorods was developed. Abstract : A highly sensitive colorimetric metalloimmunoassay with a detection limit of 0.15 ng ml −1 for human IgG based on copper-mediated etching of gold nanorods was proposed. The assay is more sensitive than traditional ELISA, electrochemical metalloimmunoassay and HRP mimic nanomaterial tag-based immunoassay.